2019
DOI: 10.1002/oby.22699
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition During Pregnancy Differs by Obesity Class

Abstract: Objective: The aim of this study is to characterize changes in body composition during pregnancy in women with obesity. Methods: Fifty-four healthy women with obesity (class 1, 30-34.9 kg/m 2 : n = 25; class 2, 35-39.9 kg/m 2 : n = 21; class 3, ≥ 40.0 kg/m 2 : n = 8) expecting a singleton pregnancy were studied. Body composition was measured in early pregnancy (13-16 weeks), midpregnancy (24-27 weeks), and late pregnancy (35-37 weeks) using air displacement plethysmography, stable isotopes, and skinfold thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Assuming a FFM accretion comparable to the other BMI classes and the inverse association between pre-gravidic BMI and FM gain throughout all BMI classes, their model suggested that maternal FM should be lost during pregnancy in cases of morbid obesity (BMI ≥ 40 kg/m 2 ) in order to optimize health outcomes (75). Body composition studies with air plethysmography confirmed that in obese women with non-excessive GWG (according to IOM), body weight was affected by changes in FM, and an inverse association between pre-gravidic BMI and FM gain was observed, with women with class 3 obesity gaining less, or loosing body weight and FM, with respect to class 1 or 2 (101).…”
Section: Gestational Weight Gain In Obesitymentioning
confidence: 84%
See 2 more Smart Citations
“…Assuming a FFM accretion comparable to the other BMI classes and the inverse association between pre-gravidic BMI and FM gain throughout all BMI classes, their model suggested that maternal FM should be lost during pregnancy in cases of morbid obesity (BMI ≥ 40 kg/m 2 ) in order to optimize health outcomes (75). Body composition studies with air plethysmography confirmed that in obese women with non-excessive GWG (according to IOM), body weight was affected by changes in FM, and an inverse association between pre-gravidic BMI and FM gain was observed, with women with class 3 obesity gaining less, or loosing body weight and FM, with respect to class 1 or 2 (101).…”
Section: Gestational Weight Gain In Obesitymentioning
confidence: 84%
“…Most et al showed that GWG in pregnancy differs by obesity classes and trimesters (101). Based on previous data of body weight and composition for pregnant women up to class 1 obesity, a linear model to predict the changes in body composition (GWG, FFM, and FM) for women with obesity class 2 and 3 and with an appropriate total GWG were elaborated.…”
Section: Gestational Weight Gain In Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…The combined lowest risks for SGA, LGA and caesarean section have been reported in a systematic review in women with Class III obesity who gained no weight overall during pregnancy [9]. Weight maintenance in obese pregnant women is likely to be achieved by an increase in fat mobilisation, as a study of body composition revealed that women with Class III obesity lose fat, in comparison to Class I and II women who gain fat, in the second trimester [25]. However, weight gain of <5 kg in pregnancy by women with Class III obesity has been shown to significantly increase the risk of low birth weight infants and neonatal mortality, relative to those gaining weight within the NAM limits [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these are outdated, and their validation studies do not include different kind of morphotypes (i.e., obese women), so the applicability of SFT equations to calculate body composition in women with obesity or overweight is unknown. Many studies have been recently published on this topic [13,26,30,31], although many of these do not explain a specific protocol for measuring skinfolds [2,26,30,31] or, in other cases [12,13,27], SFT is measured following older protocols (i.e., Lohman et al (1988) [32] or Taggart et al (1967) [33]). Lohman et al emphasize that the SFTs that better correlate with body density are the abdominal, triceps, and calf SFT.…”
Section: Discussionmentioning
confidence: 99%